The Impact of Metaverse Affecting Factors on Learning Effectiveness: A Case Study - Alhawary, Faleh Abdulqader (European Journal of Science, Innovation and Technology, 2023)
The main purpose of this study is to analyse the effect of metaverse certain factors on learning effectiveness via metaverse utilization. The population for this study consists of academic staff at the police college-Abu Dhabi. A simple random sampling technique was used to select the respondents surveyed for this study, a total of 80 questionnaires were administered to respondents; statistical tools were used to test the hypothesis such as: one way ANOVA and simple regression. The findings indicated that there were no significant differences in the perception of respondents toward the utilization of metaverse on student learning effectiveness. The study also showed that the overall of metaverse affecting factors has a significant impact on learning effectiveness, further study results have been revealed and discussed.